Dan-Shen-Yin Granules Prevent Hypoxia-Induced Pulmonary Hypertension via STAT3/HIF-1α/VEGF and FAK/AKT Signaling Pathways - Wang, Ran-Ran; Yuan, Tian-Yi; Chen, Di; Chen, Yu-Cai; Sun, Shu-Chan; Wang, Shou-Bao; Kong, Ling-Lei; Fang, Lian-Hua; Du, Guan-Hua (Frontiers in Pharmacology, 2022)
Traditional Chinese medicine (TCM) plays an important role in the treatment of complex diseases, especially cardiovascular diseases. However, it is hard to identify their modes of action on account of their multiple components. The present study aims to evaluate the effects of Dan-Shen-Yin (DSY) on hypoxia-induced pulmonary hypertension (HPH), and then to decipher the molecular mechanisms of DSY. Systematic pharmacology was employed to identify the targets of DSY on HPH. Furthermore, core genes were identified by constructing a protein-protein interaction (PPI) network and analyzed by Gene Ontology (GO) and Kyoto Encyclopedia of Genes (KEGG) analysis. Related genes and pathways were verified using a hypoxia-induced mouse model. Based on network pharmacology, 190 potential targets of DSY on HPH were found, constructing a PPI network, and 13 hub genes were predicted. The results showed that the effect of DSY may be closely associated with AKT serine/threonine kinase 1 (AKT1), signal transducer and activator of transcription 3(STAT3) and vascular endothelial growth factor A(VEGFA) pathways, as well as biological processes such as cell proliferation and redox balance. Consistent with network pharmacology analysis, experiments in vivo demonstrated that DSY could prevent the development of HPH in a hypoxia-induced mouse model and alleviate pulmonary vascular remodeling. In addition, inhibition of STAT3/HIF-1α/VEGF and FAK/AKT signaling pathways in the lung might serve as mechanisms. Taken together, the network pharmacology analysis suggested that DSY exhibited therapeutic effects through multiple targets in the treatment of HPH. The deductions were preliminarily confirmed by subsequent in vivo studies. This study provides a novel perspective for studying the relevance between TCM and disease processes and illustrates the advantage of this approach and the multitargeted anti-HPH effect of DSY.